Evidence-based medicine: assessment of knowledge of basic epidemiological and research methods among medical doctors. Issue 974 (5th December 2006) - Novack, L; Jotkowitz, A; Knyazer, B; Novack, V
Abstract : Background: An understanding of statistical methods and basic epidemiology are crucial for the practice of modern medicine. Aims: To assess (1) the knowledge of basic methods of conducting research and data analysis among residents and practicing doctors and (2) the effect of country of medical school graduation, professional status, medical article reading and writing experience on the level of this knowledge. Methods: Data were collected by means of a supervised self-administered questionnaire, which was distributed among doctors at Soroka Medical Center, Beer-Sheva, Israel. The questionnaire included 10 multiple-choice questions on basic epidemiology and statistics, and respondent demographical data. Results: Of the 260 eligible doctors, 219 (84.2%) returned completed questionnaires. Of the 219 doctors, 50% graduated more than 8.5 years ago, 39.7% were specialists and the remaining were residents. The most frequent specialty was internal medicine (37.4%). Israel was the most frequent country of graduation (45.7%), followed by the former Soviet Union (Eastern medical education; 38.4%). The median total score of knowledge was 4 of 10 questions (interquartile range 2–6). A higher score was associated with a Western medical education, being a specialist, shorter elapsed time since graduation, higher number of publications and self-reported reading of "methods" and "discussion" sections in scientific articles. Conclusion: This study found a low level of knowledge of basic principles of research methods and data analysis among doctors, and this knowledge considerably differed by country of medical school graduation.